Effect of Salinity Stress, Humic Acid and Nanochitosan on plant - ALGHABBAN, IBTISAM; Zahrani , Hassan; Alghamdi, Sameera (Journal of King Abdulaziz University-Meteorology Environment and Arid Land Agriculture Sciences, 2024)
Abstract Salinity reduces the agricultural productivity of most plants. Humic acid (HA) and chitosan nanoparticles (CNPs) offer promising benefits for sustainable agricultural production due to their natural origins and potential to be used as a treatment for the effects of salt stress, improving plant resilience and productivity so that we can avoid salt use. Water in agriculture. Or reduce the harmful effects of its use on plants, as stated in previous literature. The present review represents details about salt stress and the damages and negative effects it causes on plant growth, agricultural production, and metabolites within the plant. It also sheds light on the definition of humic acid and its composition, effective and positive role in plant growth and increasing resistance to salinity. It also clarified the importance played by nanocomposites (nano chitosan) and their role as treatments for salinity.